2014
DOI: 10.1007/s00270-014-0913-2
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Study of Preemptive Oral Oxycodone with Morphine Patient-Controlled Anesthesia for Postoperative Pain Management in Patients Undergoing Uterine Artery Embolization for Symptomatic Uterine Fibroids

Abstract: Purpose To evaluate the analgesic efficacy of oral premedication of oxycodone in a group of patients undergoing elective uterine artery embolization under sedation for fibroid disease. Methods Thirty-nine patients (mean age 42.3 years) were prospectively randomized 1:1 to receive 20 mg oxycodone or placebo orally immediately before their procedure. At the commencement of the procedure, patients were provided with a patient-controlled analgesia device for 24 h, programmed to deliver 1 mg boluses of intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
9
2
2
Order By: Relevance
“…The result of this clinical trial corresponds with the previous studies that preoperative controlled-release oxycodone could decrease postoperative pain without an increase of side effects [7,8] Our results, however, are at variance with the results of Konstantatos et al They demonstrated that the addition of preprocedural oral oxycodone to morphine PCA did not offer any analgesic advantage to patients undergoing uterine artery embolization [9]. This could be ascribed to too late administration of oral oxycodone which was administered just before the procedure.…”
Section: Discussioncontrasting
confidence: 57%
“…The result of this clinical trial corresponds with the previous studies that preoperative controlled-release oxycodone could decrease postoperative pain without an increase of side effects [7,8] Our results, however, are at variance with the results of Konstantatos et al They demonstrated that the addition of preprocedural oral oxycodone to morphine PCA did not offer any analgesic advantage to patients undergoing uterine artery embolization [9]. This could be ascribed to too late administration of oral oxycodone which was administered just before the procedure.…”
Section: Discussioncontrasting
confidence: 57%
“…Moreover, in some cases, UAE still fails to cease blood flow in the uterine artery, and embolic agents may enter the ovary and affect blood supply therein accordingly. To this end, MRI guidance is employed to shun ovarian branch of the uterine artery and to clearly display foci and the surrounding structures, thereby allowing real-time image feedback and non-axial entrance, monitoring the locations of related tissues in random directions, and minimizing injuries to normal tissues 19. In this study, the serum FSH, LH and E2 levels of the two groups were similar before treatment, which were significantly raised after treatment (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Our results, however, are at variance with the results of Konstantatos et al They demonstrated that the addition of preprocedural oral oxycodone to morphine patient-controlled analgesia did not offer any analgesic advantage to patients undergoing uterine artery embolization. 13 This could be ascribed to too late adminstration of oral oxycodone which was administered just before the procedure. It was proposed that adequate time interval between drug administration and surgical procedure was necessary for preemptive effect of oxycodone to be exhibited.…”
Section: Discussionmentioning
confidence: 99%